Study guides

Q: Evaluate 9p plus 33 for p equals 5?

Write your answer...

Submit

Related questions

9p + 27 = 9(p + 3)

-9p + 6p = -3p

9p - 5

-14 + 3p = -9p - 21 add 14 and 9p to both sides, then 12p = -7 p = -7/12

9p + 12

-10 -7 + 9p = 9p - 17

9(9p + 5r)(9p + 5r)

-9p - 15 = 93

Equilibrium occurs where Qd = QsQd - 128 + 9p = 0Qd = 128 - 9pQs + 32 - 7p = 0Qs = 7p - 327p - 32 = 128 - 9p16p = 160p = 10

allow me to answer your question with another question: why is this in the calculus section?

-9p-17=8 -17=8+9p 9p=-17-8 9p= -25 p=-25/9

Nonsense.

9p+1 = 1p+3 Take away 1p from each side: 8p+1=3 Take away 1 from each side: 8p = 2 Divide both sides by 8: p = 2/8 = 1/4

p = -3

7p+5t

4p - 12 = 3p - 8 - 9p 4p - 3p + 9p = -8 + 12 10p = 4 p = 0.4 (or 2/5)

2p - 16 = 37 + 9p(1) you need to gather like terms on each side, the variable & numbers. add 16 to both sides.2p - 16 + 16 = 37 + 9p + 162p = 53 + 9p(2) now subtract 9p from both sides to get:2p - 9p = 53+9p - 9p-7p = 53(3) now divide each side by -7-7p/-7 = 53/-7p = -53/7

3p + 6p = (3 + 6)p = 9p

15 = 5 +( 9p - 4p) 15 = 5 + 5p 15 - 5= 5 -5 +5p 10 = 5p there for p = 10/5 = 2

It is a linear equation in the one variable, p.

2p+7p = 9p simplified

64-9p = 55

9p2 + 6 - 8 = 9p2 - 2

14p + 14q + p - 7q - 6p = 9p + 7q

p2 + 9p + 18/ p + 6(p + 6)(p + 3)/ p + 6(p + 6)(p + 3)/ p + 6p + 3